The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13104-015-1478-0
|View full text |Cite
|
Sign up to set email alerts
|

External quality assessment for acid fast bacilli smear microscopy in eastern part of Ethiopia

Abstract: BackgroundExternal quality assessment (EQA) of sputum smear microscopy is essential and indispensable component of any tuberculosis program. This study assessed the EQA of acid fast bacilli (AFB) smear microscopy through onsite evaluation, blinded rechecking and panel test. A one year study was conducted on eight health institution laboratories from December 2011 to December 2012. Onsite evaluation, blinded rechecking and panel tests were used to collect data. Data were analyzed using SPSS version 16. Sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
5
8
4
Order By: Relevance
“…This was comparable with a study indicated 61.5% (13) in DRC [17]. But, higher than other ndings 23.4% in West Amhara, 21% in New delhi and (36.4%) Eastern Ethiopia [12,16,21]. The difference was attributed to methodological difference.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This was comparable with a study indicated 61.5% (13) in DRC [17]. But, higher than other ndings 23.4% in West Amhara, 21% in New delhi and (36.4%) Eastern Ethiopia [12,16,21]. The difference was attributed to methodological difference.…”
Section: Discussionsupporting
confidence: 85%
“…The smear reading agreement was substantial with kappa value 0.80. Similar ndings indicated in Eastern part of Ethiopia, K=0.84 [21]. In contrast, the agreement was lower than ndings in West Amhara, K=0.97 and Addis Abeba, K=0.87 [20,21].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Manalebh et al studied three EQA methods to assess AFB smear microscopy performance in Ethiopia: on-site evaluation, blinded rechecking and panel testing; poor staining and low positivity were major factors affecting PT performance ( 49 ). Ayana et al employed similar mixed approaches to assess AFB smear microscopy at university practical attachment sites in Ethiopia; poor working environments were a major contributor to poor performance ( 50 ). Some studies noted re-staining during rechecking at national level significantly improved sensitivity of low-positive AFB smears ( 41 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…EQA schemes are valuable for recognising laboratory errors and identifying underlying problems facing peripheral laboratories ( 50 ), but participation in PT schemes may not by themselves improve performance. Mandy et al and Mukadi et al .…”
Section: Resultsmentioning
confidence: 99%